1995
DOI: 10.1093/jaoac/78.3.802
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Fat, Protein, and Total Solids in Cheese by Near-Infrared Reflectance Spectroscopy

Abstract: Near-infrared reflectance (NIR) spectroscopy was used to analyze fat, protein, and total solids in cheese without any sample treatment. A set of 92 samples of cow’s milk cheese was used for instrument calibration by principal components analysis and modified partial least-square regression. The following statistical values were obtained: standard error of calibration (SEC) = 0.388 and squared correlation coefficient (R2) = 0.99 for fat, SEC = 0.397 and R2 = 0.98 for protein, and SEC = 0.412 and R2 = 0.99 for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(24 citation statements)
references
References 0 publications
1
21
1
1
Order By: Relevance
“…Reflectance near-infrared spectroscopy has been reported for the determination of chemical constituents in varieties of hard and semihard cheeses. Similar performance statistics were reported for near-IR with R 2 > 0.92 and SEP values ranging from 0.3 to 0.6% for moisture, 0.3 to 0.5% for fat, and 0.3 to 0.5% for protein, depending on the type of cheese and mathematical transformation of the spectral data (Pierce and Wehling, 1994;Rodriguez-Otero et al, 1995;Sorensen and Jepsen, 1998;Wittrup and Nørgaard, 1998;Mazerolles et al, 2000). Improved prediction results have been reported for near-IR analysis of processed cheeses, with SEP of 1.25 and 1.24 g/kg for moisture and fat, respectively, probably due to the less heterogeneous composition of the cheese material (Adams et al, 1999).…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Reflectance near-infrared spectroscopy has been reported for the determination of chemical constituents in varieties of hard and semihard cheeses. Similar performance statistics were reported for near-IR with R 2 > 0.92 and SEP values ranging from 0.3 to 0.6% for moisture, 0.3 to 0.5% for fat, and 0.3 to 0.5% for protein, depending on the type of cheese and mathematical transformation of the spectral data (Pierce and Wehling, 1994;Rodriguez-Otero et al, 1995;Sorensen and Jepsen, 1998;Wittrup and Nørgaard, 1998;Mazerolles et al, 2000). Improved prediction results have been reported for near-IR analysis of processed cheeses, with SEP of 1.25 and 1.24 g/kg for moisture and fat, respectively, probably due to the less heterogeneous composition of the cheese material (Adams et al, 1999).…”
Section: Resultssupporting
confidence: 72%
“…Near infrared and mid-IR spectroscopy have been extensively used for the analysis of several milk components such as protein, fat, moisture, sugars, casein, cholesterol, and contaminants such as tetracycline (Rodriguez-Otero et al, 1997;O'Sullivan et al, 1999;Tsenkova et al, 1999;Luginbü hl, 2002;Paradkar and Irudayaraj, 2002;Sivakesava and Irudayaraj, 2002;Sorensen et al, 2003). Near-infrared spectroscopy has been widely studied for the rapid determination of major cheese constituents such as protein, fat, moisture, DM, and total solids (Frank and Birth, 1982;Wehling and Pierce, 1988;Pierce and Wehling, 1994;Rodriguez-Otero et al, 1995;McQueen et al, 1995;Wittrup and Noøgaard, 1998;Adamopoulos et al, 2001;Č urda and Kukačková , 2004). On the contrary, few studies have reported the application of midIR spectroscopy for cheese analysis because of difficulties in the sampling procedures due to the lack of homogeneity of the components in the cheese (McQueen et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Spectra within each treatment group were centred to detect any outliers of data, using 3.0 as the cut-off H value. 19 No outliers were found in the present study. At the end of spectroscopic analysis, minced meat samples were stored in airtight plastic bags at À30°C for further chemical analysis.…”
Section: Spectroscopic Analysiscontrasting
confidence: 43%
“…The chemical reference methods for measurement of fat (e.g., Babcock and Mojonnier ether extraction), CP (Kjeldahl), moisture (forced air oven-drying), and salt (Volhard silver nitrate titration) are accurate but are too slow and impractical for rapid analysis of large numbers of cheese samples in a commercial quality assurance (QC) laboratory. Therefore, more rapid and cost-effective methods such as near-infrared (NIR) reflectance for fat, protein, and moisture (Rodriguez-Otero et al, 1995;McKenna, 2001) and coulometric methods (Varcoe, 2001) for salt determination are currently used in cheese factories.…”
Section: Introductionmentioning
confidence: 99%